Confucian Depth Ecology as a Response to Climate Change - James D. Sellmann (Religions, 2025)
Aside from a few passages addressing animals or the environment, Confucian philosophy appears to lack an environmental ethics perspective. Li Zhehou’s (李澤厚) contemporary work in Confucian philosophy continues this lacuna by limiting his understanding of community to the human realm. Using the common liberal humanism that limits moral actions to the interpersonal human realm misses the importance of inclusive moralities such as animal rights and environmental ethics. I propose that if we return to the original shared common cultural roots of Confucian and Daoist philosophy that a Confucian understanding of the natural world can embrace the non-human environment within the scope of Confucian morality. Extricating ideas from the Yijing, the Shijing, Xunzi, Dong Zhongshu, Wang Chong, and later scholars, the concept of the mutual resonance and response (ganying 感應) between the natural world and humans developed into the unity of heaven and humanity (tianren heyi 天人合一). An inclusive Confucian depth ecology opens new ways of thinking that can be deployed to envision deeper dimensions for understanding the self’s inner life, its connections to the outer life of the self–other relationship, and its extension to a kin relationship with the environment. This paper explores how these old and new ways of thinking can change our behavior and change our moral interactions with others including the environment and thereby enhancing freedom as an achievement concept derived from graceful moral action.